Działalność Instytutu Filologii Polskiej Uniwersytetu Zielonogórskiego na łamach rocznika w latach 2015-2024 (numery 1-10) = The activities of the Institute of Polish Philology at the University of Zielona Góra in the pages of the yearbook in the years 2015-2024 (issues 1-10) - Jabłońska, Izabela; Majkowska, Michalina; Sztyber, Radosław (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article provides an overview of the activities of the Institute of Polish Philology at Zielona Góra University, as consistently documented in the pages of its annual journal from 2015 to 2024. It takes into account both recurring and occasional initiatives, publishing series (such as "Zielonogórskie Seminaria Językoznawcze" or "Scripta Humana"), thematic competitions (in the fields of Polish literature, language, and media studies), academic conferences (such as the 13th Forum of Word Culture or the Mickiewicz Symposium commemorating the 160th anniversary of the poet`s death), and more. A separate section briefly revisits the profiles of the Institute`s academic staff featured in successive issues of the journal, includ-ing: Marian Bugajski, Jerzy Brzeziński, Czesław Paweł Dutka, Maria Januszewicz, Leszek Libera, Krzysztof Maćkowiak, Ireneusz Sikora, Anna Szóstak, and Marzanna Uździcka.
Keywords: Uniwersytet Zielonogórski - Instytut Filologii Polskiej; polonistyka zielonogórska; "Filologia Polska. Roczniki Naukowe Uniwersytetu Zielonogórskiego" - czasopismo; University of Zielona Góra - Institute of Polish Philology; Polish studies in Zielona Góra